2021
DOI: 10.2507/ijsimm20-2-562
|View full text |Cite
|
Sign up to set email alerts
|

Formation Mechanism of an Adherent Vortex in the Side Pump Sump of a Pumping Station

Abstract: The inflow of the side pump sump is not smooth enough during the operation of a pumping station, resulting in an asymmetric adherent vortex that endangers the station's normal operation and safety. To solve this problem, flow field and vorticity distribution charts of different flow layers were created through the establishment of a numerical model of the pumping station inflow by means of the fluid simulation software. The formation mechanism of the asymmetric adherent vortex in the side pump sump was analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…This approach yielded an 8% enhancement in the uniformity of the flow velocity in the front pool, as well as an impressive 70% reduction in the vortex area. By employing the image velocimetry technique, Xi and Lu [15] acquired flow field data from both the front and inlet tanks of the pump station, subsequently substantiating these data through comprehensive numerical simulations. This research findings notably revealed an asymmetrical nature of the inlet vorticity in the forebay of the lateral pumping station.…”
Section: Introductionmentioning
confidence: 98%
“…This approach yielded an 8% enhancement in the uniformity of the flow velocity in the front pool, as well as an impressive 70% reduction in the vortex area. By employing the image velocimetry technique, Xi and Lu [15] acquired flow field data from both the front and inlet tanks of the pump station, subsequently substantiating these data through comprehensive numerical simulations. This research findings notably revealed an asymmetrical nature of the inlet vorticity in the forebay of the lateral pumping station.…”
Section: Introductionmentioning
confidence: 98%
“…At the same time, a gradually increasing number of researchers are applying numerical simulations of the forebays of pump stations. Xi and Lu 6 analyzed the formation mechanism of nonsymmetric adhesive vortices in lateral pumping stations by using numerical simulation combined with Reynolds shear stress distributions. Jie-min et al 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [2] used the CFD method to simulate the three-dimensional turbulent flow in the coupled half-elbow sump of a large diameter axial flow pump, and found that there were increases in an obvious reflux phenomenon in the half-elbow sump and strong flow inhomogeneity at the outlet of the sump. Based on Reynolds shear stress distribution, a simplified Navier-Stokes equation, and a turbulent kinetic energy transport equation, Xi et al [3] analyzed the formation mechanism of asymmetrically attached vortices in the side pump sump. Padmanabhan et al [4] analyzed the scale effect of the experimental model of inflow flow.…”
Section: Introductionmentioning
confidence: 99%